(untitled) (Experimental biology, 2016)
Malnutrition in low-income countries is one of principal issues so far unresolved. The scholars are being urged to suggest effective means for better nourishing by using updated methods of breeding and harvesting. Beans are considered as the major resource of vegetable protein among plants. Beans are enriched by vitamins, minerals, flavanoids, fiber, and are also appropriate for cropping under the steppe as mountain conditions. Under arid conditions beans are regarded as useful tool for explorating those areas which are unsuitable for obtaining steady annual harvests. This paper summes up the data on the introduction and breeding of a range of common bean varieties representing local and foreign specimes. It overviews the data on biochemical comparison of different bean varieties, and amino acids composition of the seeds. Present-day bean production in Kazakhstan is complied mainly with imported seeds, raw and canned beans from CIS and foreign countries. Meanwhile, southeast regions of this country are extremely favourable for the cropping of high-protein bean varieties. Modern beans breeding is not supported by relevant physiological and biochemical investigations which would allow to evidence in favour of the impact of changing plant morphogenetic traits on biochemical characters, physiological functions, seed productivity, grain quality and plant adaptiveness to be inherited by the following generations. The aim of current study is to generate high-protein lines of common bean, put forward their qualitative characteristic based on bean breeding and extensive bean introduction. Бұршақты дақылдар барлық өсімдіктердің ішінде ақуызға ең бай болып саналады. Бұл дақылдарда дәрумендер, минералдар, флавоноидтер, өсімдік талшықтары мол және олар жазықта да таулы жерлерде де өсе береді. Құрғақшылық кезінде бұршақты дақылдар жыл сайын тұрақты мөлшерде алынатын өнімдер қатарына жатады. Бұл мақала үрмебұршақтың жергілікті және халықаралық жаңа сұрыптарын жерсіндіру мен өсіру туралы мәліметтерді жинақтайды. Мақалада үрмебұршақты биохимиялық салыстыру талқыланды, сонымен қатар тұқымдардың аминқышқылды құрамы қаралады. Қазіргі селекцияда бұршақ тұқымдастарға физиология-биохимиялық зерттеулерде қолдау нашар көрсетіліп жүр; бұл зерттеулер морфогенетикалық белгілердің биохимиялық өзгерістерге, физиологиялық ерекшеліктерге өсімдіктердің бейімделуіне, тұқымдардың өнімділігіне және сапасына, тұқымдарға әсер етеді. Бобовые культуры являются чемпионом среди растений как основной источник растительного белка. Эти культуры обогащены витаминами, минеральными элементами, флавоноидами, растительным волокном и универсальны для возделывания в степной и горной зонах. В засушливых условиях бобовые рассматриваются как подходящие культуры для анализа спорных зон на предмет получения стабильных и ежегодных урожаев. Данная статья суммирует данные по интродукции и получению новых сортоформ фасоли, представляющих международные и местные сортообразцы. В статье обсуждаются данные по биохимическому сравнению сортообразцов фасоли, аминокислотному составу семян. Современная селекция бобов слабо поддерживается физиолого-биохимическими исследованиями, которые указывают на влияние изменяющихся морфогенетических признаков на биохимические свойства, физиологические свойства, адаптивность растений, продуктивность и качество семян, наследуемые следующими поколениями.